Real-Time Ultrasound Imaging of the Tear Trough: Lessons Learned From Functional Anatomy. (5th October 2021) - Calomeni, Mariana; Alfertshofer, Michael G; Frank, Konstantin; Moellhoff, Nicholas; Dennison, Rebekah; Bravo, Bruna; Schelke, Leonie; Velthuis, Peter; Green, Jeremy B; Cotofana, Sebastian
Abstract: Background: The tear trough is one of the most challenging facial regions for soft-tissue filler injections. A thorough understanding of the underlying facial, muscular, and vascular anatomy is crucial to perform safe and effective tear trough injectable treatments. Objectives: The authors sought to evaluate the location and function of the angular vein in the tear trough in 3 different facial expressions: repose, smiling, and max. orbicularis oculi contraction. Methods: Twenty study participants with a mean age of 48.3 years and mean BMI of 24.5 kg/m 2 were investigated via functional ultrasound imaging. The diameter of the angular vein and the velocity and direction of venous blood flow were analyzed in repose, smiling, and during max. orbicularis oculi contraction. Results: The angular vein was identified in 100% of the cases to travel inside the orbicularis oculi muscle (intra-muscular course) within the tear trough, whereas the angular artery was not identified in this location. The distance between the angular vein and the inferior orbital rim was (lateral to medial): 4.6 mm, 4.5 mm, 3.9 mm, and 3.8 mm. The caudally directed blood flow was in repose 10.2 cm/s and was 7.3 cm/s at max. orbicularis oculi muscle contraction; however, no blood flow was detectable during smiling. Conclusions: The diameter and the venous blood flow of the angular vein varied between the 3 tested facial expressions. Based on these anatomical findings, the deep injection approach to the tear trough is recommended due to the intramuscular course of the angular vein.